Analysis of Air Pollution Trajectory Using the HYSPLIT Model - Tarif, Eqiu Alkahfi; Budhicahyanto, Moehammad; Darojat, Khumaidah (Journal of Engineering Science and Technology Management, 2025)
The growth of industrial activities has contributed significantly to the increase in air pollutant emissions, adversely affecting human health and environmental quality. Understanding the direction and potential dispersion of air pollutants is therefore a crucial aspect of air pollution control efforts, particularly for mitigating transboundary and transregional impacts. This study aims to analyze the movement trajectories of air pollutants released from industrial stacks using the Hybrid Single-Particle Lagrangian Integrated Trajectory (HYSPLIT) model. Forward trajectory simulations were conducted for a duration of 240 hours (10 days) using meteorological data from the Global Forecast System (GFS). The emission source was assumed to be located in the Perawang industrial area, with a stack height of 100 meters above ground level. The simulation results indicate that during the dry season (East Monsoon), the dominant direction of air mass movement tends to be northward to northeastward, crossing the Malacca Strait and potentially reaching regions of Malaysia, Thailand, Vietnam, and southern China. These findings suggest a significant potential for long-range and transboundary transport of air pollutants, highlighting the need for strengthened industrial emission control and enhanced regional cooperation in air pollution management.